Os Fundamentos da Física Aplicados em Situações Cotidianas: Um Estímulo para Aumentar o Interesse dos Alunos - Valério, Rita de Cássia [UNESP] (2015)
Discussions about the best educational model for Education in Brazil is, today, still very comum. These discussions are consequences of the education actually be a process in constant development, in which discuss what kind of teacher and student is desired to build a nation of competent and critical citizens, and still, if the goal of the educational process aims to reproduce or transform society in which the student mass is inserted. In the midst of so many challenges and prospects, the teacher becomes the main mediator responsible for building the society of the future, and it is in this context that this work is inserted. With regard to the Physics teaching, is proposed for this work, the adoption of strategies and a new methodological approach, which aims to enhance the learning of high school students, as well as, awaken their curiosity, encouraging searching and construction of new knowledge. Appropriating of the Ausubel significant learning theory and unconventional tools of education, electromagnetism themes were developed considering the daily life of students, and show where and how the Physics is inserted in life each. Questionnaires were applied to students to direct the didactic and also used to verify and evaluate the methodology used by the educator...